Us and Them: The Role of Group Identity in Explaining Cultural Resonance and Framing Effects. Issue 2 (4th March 2023) - Sheets, Penelope; Rowling, Charles M.; Gilmore, Jason; Melcher, Niklas
ABSTRACT: This study investigates the importance of group identity as a determinant of cultural resonance in news framing effects research. Two parallel survey experiments were conducted in the United States and Britain; respondents received a news story about a military atrocity attributed to either American or British soldiers during the war in Afghanistan. In one condition, the story contained only basic facts about the incident. In the other, the story included frames reinforcing the national identity of the accused nation, including: (a) downplaying the incident; (b) denigrating the transgressors; and (c) redirecting attention toward positive aspects of the nation. We find that these frames tend to be more powerful when protecting ingroup (versus outgroup) identity. The reason, we argue, is due to their cultural resonance, not simply the factual information that they make salient. More broadly, our results offer important insights into the framing process, illuminating the psychological mechanisms that help explain how cultural resonance can facilitate specific responses among audiences, particularly in response to group identity threats.